Fast Tracking of Detection Offenders Smoking Zone Menggunakan Sensor MQ-2 Berbasis Internet of Things - Fredy Susanto; Syafnidawati Syafnidawati (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2018)
With the increasing violations by smokers in free zone cigarettes, very affecting for human health cigarettes or not smokers. So that designed a supervision system to reduce the number of violations by smokers. The system is based on the aimed to detect and provide a warning to smokers that the room cannot be cigarettes if breaking will be imposed sanctions. This system is made up of hardware, consists of smoke sensor base their MQ2, Camera C270 and Raspberry pi. This system created by the language of Python programming technique. How this appliance if violations by smokers, when smoke is detected then the webcam will take pictures of the offenders and the results of the photo will be sent automatically to the email, if the results of the photo has been sent to email and alert sound alarm will be active and a notification that in the area cannot be cigarettes. The results of the design of this system is not only to detect and provide a notification only, but it also has been able to give a warning and evidence of who is a breach in the zone. Index Terms— Smoke sensor, MQ-2, raspberry pi